ANALISIS YURIDIS TERHADAP PENYALAHGUNAAN NARKOTIKA OLEH ANAK DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Herlina Isang; Muhamad Chaidar (Fakultas Ilmu Sosial dan Humaniora, 2026)
This research discusses legal protection for children who abuse narcotics within the juvenile criminal justice system in Indonesia. The main focus of the study is the legal framework regulating the position of children as perpetrators, victims, or witnesses, as well as the duality between criminal law enforcement and rehabilitation approaches. The research employs a qualitative method with a normative juridical approach, involving an analysis of legislation, literature, and case studies. This approach includes examining the provisions contained in Law Number 35 of 2009 on Narcotics and Law Number 11 of 2012 on the Juvenile Criminal Justice System, as well as reviewing doctrines and theories of criminal law and child protection theories, supported by case studies related to the issue.